Current Scales and Questionnaires for Assessing Stress Conditions and Their Application in Medicine: a Review - Anna A. Kuzyukova; Yana G. Pekhova; Olga I. Odarushenko; Natalia A. Levchenko; Larisa A. Marchenkova (Вестник восстановительной медицины)
INTRODUCTION. Stress can act as an etiological factor in about 80 % of diseases, its impact on health is multifaceted and the burden of stress continues to grow. Currently, every fifth adult in Russia experiences a high level of psychoemotional stress. Stressful conditions are characterized by a high prevalence, which contributes to the high incidence of patients with vegeto-somatic symptoms of stress in non-psychiatric medical institutions, where the detection of these disorders is difficult. The search and development of optimal diagnostic methods for stress-related psychosomatic disorders remains a very important and urgent problem.